Speciation and phylogeography of giant petrels Macronectes - Techow, N. M. S. M. (2010)
We examine global phylogeography of the two forms of giant petrel Macronectes spp. Although previously considered to be a single taxon, and despite debate over the status of some populations and the existence of minimal genetic data (one mitochondrial cytochrome b sequence per form), the current consensus based on morphology is that there are two species, Northern Giant Petrel M. halli and Southern Giant Petrel M. giganteus. This study examined genetic variation at cytochrome b as well as six microsatellite loci in giant petrels from 22 islands, representing most island groups at which the two species breed. Both markers support separate species status, although sequence divergence in cytochrome b was only 0.42% (corrected). Divergence was estimated to have occurred approximately 0.2 mya, but with some colonies apparently separated for longer (up to 0.5 my). Three clades were found within giant petrels, which separated approximately 0.7 mya, with the Southern Giant Petrel paraphyletic to a monophyletic Northern Giant Petrel. There was evidence of past fragmentation during the Pleistocene, with subsequent secondary contact within Southern Giant Petrels. The analysis also suggested a period of past population expansion that corresponded roughly to the timing of speciation and the separation of an ancestral giant petrel population from the fulmar Fulmarus clade. © 2009 Elsevier Inc. All rights reserved.